Requirements for engineer information in water crossing - Martin Sedláček; Jaroslav Zelený (Vojenské rozhledy, 2019)
The work deals with the issue of engineer information, which is necessary for the planning of water crossing, and which can facilitate and speed up the proces of operation planning with the assistance of the staff members of engineer specialization. At present (2019) there is no application software development of engineer support tasks (hereinafter APV ŽEN) within the engineer command and control subsystem AČR, which would take into account the problem of water crossing by troops. The aim of the article is: to analyze the gathering of engineer information for water crossing and to describe it on a specific example of the Morava river, to identify the possibilities of water crossing by forces of AČR, to propose a map base for APV ŽEN, which will be supplemented by engineer information from Povodí s.p. and Motorway and Highway Directorate (hereinafter ŘSD) and to define measures that will support the availability of engineer information in water crossing.